UPAYA MENINGKATKAN MOTIVASI GURU DALAM MENYUSUN SILABUS DAN RPP MELALUI SUPERVISI KEPALA SEKOLAH DI SMA NEGERI 2 TANAH PUTIH KABUPATEN ROKAN HILIR: (Effort to improve Teachers’ motivation in Preparing Syllabus and Lesson Plan through Headmaster Supervision at SMA Negeri 2 Tanah Putih Kabupaten Rokan Hilir ) - Rusnarwati Rusnarwati (UIR Press, 2017)
Teachers not only served as an educator and teacher, but the teacher is also obliged to prepare the syllabus and learning tools such as Learning Implementation Plan (RPP). The function of the learning device is to provide direction implementation of learning to become focused and efficient. The purpose of this study was to determine the increased motivation of teachers SMAN 2 Tanah Putih Rokan Hilir in preparing the syllabus and Learning Implementation Plan (RPP) through training. This research was conducted at SMAN 2 Tanah Putih Rokan Hilir in August-October 2015. This type of research is Action Research School (PTS). Action Research School (PTS) is designed for the improvement or enhancement of teacher motivation in preparing syllabus and lesson plans. The procedures in this study were shaped cycle. Data collection through qualitative data obtained from observation, observation, and interviews. Data were analyzed using descriptive comparative analysis. Indicators of success is the teacher collects research syllabus and lesson plans with good criteria is increasing every cycle of at least 10%. The findings in this study is the implementation of the supervision of the principal in this study proved to increase the motivation of teachers in preparing the syllabus and RPP at SMAN 2 Tanah Putih Rokan Hilir academic year 2014/2015.